Oh Angry Sea (a-ab-ba hu-luh-ha). The History of a Sumerian Congregational Lament - Kutscher, Raphael (1975)
photos YBC 4659 and CNM 10051 (= JCS 8,82f.), copy VAT 7824 ( = Nötscher, Ellil Taf. I-II).